2020
DOI: 10.3389/fmed.2020.00353
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Rik-203 Contributes to Sevoflurane Induced Neurotoxicity?

Abstract: Background: The anesthetics inhibit neural differentiation, induce neuron loss and cognitive impairment in young animals. However, the underlying mechanisms of anesthesia on neural differentiation are unknown. Methods: Embryonic stem cells (ESCs) and mice received sevoflurane anesthesia. RNA sequencing; gene expression of mRNAs, LncRNAs and miRNAs; over-expression and RNA interference of genes; flow cytometry; real-time quantity PCR and Western blot were used in the studies. RNA pull-down assay and PCR were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…As is well known, lncRNAs are related to many biological processes during development (such as neuronal development, plasticity, disease, and evolution) and are related with sevoflurane [ 19 , 20 ]. For example, overexpression of Gm15621 [ 21 ] or knockdown of Gm43050 [ 22 ] both attenuates sevoflurane-induced neuronal apoptosis and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, lncRNAs are related to many biological processes during development (such as neuronal development, plasticity, disease, and evolution) and are related with sevoflurane [ 19 , 20 ]. For example, overexpression of Gm15621 [ 21 ] or knockdown of Gm43050 [ 22 ] both attenuates sevoflurane-induced neuronal apoptosis and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…With its analgesic and anesthetic effect, Sev also has roles in neuronal injury and oncogenesis (Lu et al 2020;. In Sev promotion or suppression of neuronal dysfunction, non-coding RNAs, including lncRNAs and miRNAs are differently expressed, and the dysregulation of these RNAs can alter downstream functional genes in neural progenitor cells (Zhang et al 2019(Zhang et al , 2020a and hippocampal neurons (Chen et al 2016;Wang JY et al 2018;).…”
Section: Discussionmentioning
confidence: 99%
“…Several years ago, a microarray study revealed that long non-coding RNAs (lncRNAs) together with their messenger RNAs (mRNAs) targets were abnormally expressed in Sev-induced hippocampal neuronal apoptosis (Chen et al 2016). Since then, many studies have shown that lncRNAs are involved in Sev-induced neurontoxicity via serving as naturally competing endogenous RNAs (ceRNAs), such as Rik-203/microRNA (miRNA)-466l-3p/brain-derived neurotrophic factor (Zhang et al 2020a). LncRNAs are a group of >200 bp RNAs and show specific spatiotemporal expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small noncoding RNAs that can bind to the 3'-untranslated region (3'-UTR) of the transcript of their homologous target genes, thereby regulating their expression [9]. Extensive studies have confirmed a broad association between miRNAs and anesthesia-related cognitive impairment [9][10][11]; miRNAs, such as miR-665, miR-572, and miR-181, have been reported to affect POCD progression, suggesting that these miRNAs could serve as promising therapeutic targets for treating POCD [12].…”
Section: Introductionmentioning
confidence: 99%